A Survey on Power Cut Reporting and Analysis using Data Mining - Mahalakshmi; Shrivastava, Yashraj; Kumar, Mohit (International Journal of Psychosocial Rehabilitation, 2020)
To realize the idea of Digital India, we aim to bring all the electricity consumers of India on an online platform where their concerns can be heard and proper action can be taken as soon as possible. In recent years a number of new procedures with that aim to digitize the consumer platform in the domain of electricity have come up. The purpose of survey paper is to survey a number of promising techniques and technologies. Our problem statement aims to solve the power cut reporting issue for household users without any bias of region and consumption capacity to provide an analysis and monitoring of power cuts, and in our paper we aim to find the soundest approaches and latest technologies available to achieve it.